Congenital abnormalities associated with microtia: A 10-YEARS retrospective study. (July 2021) - Paul, Antoine; Achard, Sophie; Simon, François; Garcelon, Nicolas; Garabedian, Erea Noel; Couloigner, Vincent; Celerier, Charlotte; Denoyelle, Françoise
Abstract: Objective: Microtia is a congenital auricular malformation, often part of a syndromic form (35%–55% of cases). The accurate prevalence of associated malformations remains to be determined with regard to the heterogeneous results of the previous studies. This study aims to describe in a large population cohort the abnormalities associated with microtia and to determine the most suitable assessment for these children. Methods: This is a retrospective and observational cohort study collecting data from the medical records of children affected by microtia, diagnosed or followed-up between 2007 and 2017. Data were collected via a computer database. Clinical data, as well as imaging or genetic results, were noted. Results: Six hundred ninety four children were included, 587 (84.6%) with unilateral and 107 (15.4%) with bilateral microtia. Inner ear malformations were observed in 14.1% of the ears. The main associated anomalies were hemifacial microsomia (29%), velopharyngeal insufficiency (9%), ophthalmologic (6.2%), vertebral (5.9%), cardiac (5.5%) and kidney (3%) abnormalities. Main identified entities were Goldenhar, Treacher-Collins and Guion-Almeida syndromes. Conclusion: A comprehensive clinical assessment must be completed when microtia is diagnosed. Besides screening well-known oculo-auriculo-vertebral spectrum malformations, velopharyngeal insufficiency should be systematically sought. Specialized care must be provided to the very frequently associated hemifacial macrosomia. Mild forms of this last malformation may correspond to Guion-Almeida syndrome, especially in cases of learning disability.